Structural basis of antigen recognition: crystal structure of duck egg lysozyme. Issue 11 (2nd November 2017) - Langley, David Brent; Crossett, Ben; Schofield, Peter; Jackson, Jenny; Zeraati, Mahdi; Maltby, David; Christie, Mary; Burnett, Deborah; Brink, Robert; Goodnow, Christopher; Christ, Daniel
Abstract : Lysozyme isoforms purified from duck eggs have been characterized by crystallography, mass spectrometry and their capacity to bind landmark antibodies. Abstract : Duck egg lysozyme (DEL) is a widely used model antigen owing to its capacity to bind with differential affinity to anti‐chicken egg lysozyme antibodies. However, no structures of DEL have so far been reported, and the situation had been complicated by the presence of multiple isoforms and conflicting reports of primary sequence. Here, the structures of two DEL isoforms from the eggs of the commonly used Pekin duck ( Anas platyrhynchos ) are reported. Using structural analyses in combination with mass spectrometry, non‐ambiguous DEL primary sequences are reported. Furthermore, the structures and sequences determined here enable rationalization of the binding affinity of DEL for well documented landmark anti‐lysozyme antibodies.